EULAR/ERA-EDTA recommendations for the management of ANCA-associated vasculitis. Issue 9 (23rd June 2016) - Yates, M; Watts, R A; Bajema, I M; Cid, M C; Crestani, B; Hauser, T; Hellmich, B; Holle, J U; Laudien, M; Little, M A; Luqmani, R A; Mahr, A; et al.
Abstract : In this article, the 2009 European League Against Rheumatism (EULAR) recommendations for the management of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) have been updated. The 2009 recommendations were on the management of primary small and medium vessel vasculitis. The 2015 update has been developed by an international task force representing EULAR, the European Renal Association and the European Vasculitis Society (EUVAS). The recommendations are based upon evidence from systematic literature reviews, as well as expert opinion where appropriate. The evidence presented was discussed and summarised by the experts in the course of a consensus-finding and voting process. Levels of evidence and grades of recommendations were derived and levels of agreement (strengths of recommendations) determined. In addition to the voting by the task force members, the relevance of the recommendations was assessed by an online voting survey among members of EUVAS. Fifteen recommendations were developed, covering general aspects, such as attaining remission and the need for shared decision making between clinicians and patients. More specific items relate to starting immunosuppressive therapy in combination with glucocorticoids to induce remission, followed by a period of remission maintenance; for remission induction in life-threatening or organ-threatening AAV, cyclophosphamide and rituximab are considered to have similar efficacy; plasma exchange which is recommended, where licensed, in the setting of rapidly progressive renal failure or severe diffuse pulmonary haemorrhage. These recommendations are intended for use by healthcare professionals, doctors in specialist training, medical students, pharmaceutical industries and drug regulatory organisations.